2011
DOI: 10.18356/7ce1ee2d-en
|View full text |Cite
|
Sign up to set email alerts
|

Innovation, R&D investment and productivity in Chile

Abstract: This paper uses two sources of information and different methodologies to analyze the causal effect of product and process innovation on productivity in the Chilean manufacturing industry during the past decade. In general, the evidence suggests there is not a contemporaneous effect of product innovation on productivity, but there is a positive effect of process innovation. This notsignificant effect of product innovation contrasts with evidence of studies for other countries. However, the results show the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Likewise, despite dense monoaminergic innervation of the ventral horn MNs , no appositions were observed between 5-HT-immunoreactive terminals and SK3 clusters. Finally, there was no overlap or relationship between SK3-immunoreactivity and immunostaining for gephyrin, a postsynaptic scaffolding protein present at inhibitory glycinergic and GABAergic synapses on MNs (Alvarez et al 1997).…”
Section: Specific Association Of Postsynaptic Sk3 Channels and Presynmentioning
confidence: 89%
See 1 more Smart Citation
“…Likewise, despite dense monoaminergic innervation of the ventral horn MNs , no appositions were observed between 5-HT-immunoreactive terminals and SK3 clusters. Finally, there was no overlap or relationship between SK3-immunoreactivity and immunostaining for gephyrin, a postsynaptic scaffolding protein present at inhibitory glycinergic and GABAergic synapses on MNs (Alvarez et al 1997).…”
Section: Specific Association Of Postsynaptic Sk3 Channels and Presynmentioning
confidence: 89%
“…Kv2.1 immunohistochemistry was performed using mouse anti-Kv2.1 clone D4/11 at 1:1000 dilution that was developed and/or obtained from the UC Davis/NINDS/NIMH Neuromab facility, supported by NIH grant U24NS0506060 and maintained by the Department of Pharmacology, School of Medicine, University of California (Davis, CA, USA). All primary antibodies were diluted in PBS-T 0.1%, pH 7.4, and incubated overnight at 4 • C. The sensitivity and specificity of the primary antibodies against the various synaptic proteins and neuronal markers have been previously described by researchers in our laboratory (Alvarez et al 1997(Alvarez et al , 1999Deng & Fyffe, 2004;Muennich & Fyffe, 2004). Immunoreactivity was detected with species-specific secondary antibodies conjugated to fluorescein isothiocyanate, Cy3 or DyLight 649 (Jackson J Physiol 591.4 Immunoresearch, West Grove, PA, USA) diluted 1:50 in PBS-T 0.1%, pH 7.4, and incubated at room temperature for 2-4 h. Given that the antibodies against SK3 and SK2 were raised in the same host species (rabbit), the coexpression studies employed a sequential immunostaining process.…”
Section: Dual Labelling Immunohistochemical Studiesmentioning
confidence: 99%
“…Finally, two recent studies of Álvarez et al () and Demmel et al () analyze the case of innovation for manufacturing firms in Chile, and that of Argentina, Mexico, Colombia, and Peru. The Chilean study found that: larger plants are more likely to invest in R&D; R&D intensity increases the probability of process innovation; R&D intensity does not affect the probability of product innovation; low appropriability reduces the probability of process innovation; larger firms are more likely to introduce product innovation; and the process innovation increases productivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, sources of information (i.e. INFO jit ; for j = 1, 2, 3) for innovation and techological resources as the use of infomation and communication technologies ( D ICTit ) and availability of research infrastructure ( D INFRAit ) are introduced as in Álvarez et al (), Griffith et al (), and Surroca and Santamaría ().…”
Section: Cdm Model Of Innovation and Total Factor Productivitymentioning
confidence: 99%
“…Some exceptions (from Table ) that account for some dynamics in the relationship between innovation and productivity are Arza and López () and Chudnovsky, López, and Pupato (), for Argentina, and Cassoni and Ramada (), for Uruguay, who exploit the panel dimension of their data. Also, Alvarez, Bravo‐Ortega, and Navarro () and Benavente and Bravo (), for Chile, Arbeláez and Torrado (), for Colombia, and Tello (), for Peru, who consider possible delayed effects of innovation outputs on productivity. However, to the best of our knowledge, we are only aware of three studies that use TFP measures to analyze the relationship between innovation outputs and productivity in Latin America.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%